Genitalia sibi devinxit - MOGA, Iulian (Studia Universitatis Babeș-Bolyai Historia, 2025)
Issued from a rather insignificant Oriental sacerdotal dynasty of a semi-nomadic ancestry, Elagabalus seemed unfit to rule an Empire whose imagery of power and religious traditions varied considerably from those deeply embedded into the minds of his people of origin. His typical conduct, even if seen immoral, pervert, depraved, etc. could be perceivable through the perspective of a well-defined cultural Eastern legacy. It was not for the first time when the Romans encountered and coped with Oriental cults and customs on their soil, due to their having adopted the Idaean Mother along with her own chorus cinaedorum that dissuaded poets like Juvenal. But to fully support an Oriental-type sovereign trying to replace values of their own, that was hardly bearable. Rezumat: Provenit dintr-o dinastie sacerdotală orientală mai degrabă modestă, cu o ascendență semi-nomadă, Elagabalus părea nepotrivit să conducă un Imperiu ale cărui imagini ale puterii și tradiții religioase se deosebeau considerabil de cele adânc înrădăcinate în mentalitățile poporului său de origine. Comportamentul său tipic, chiar dacă era considerat imoral, pervers, depravat etc., ar putea fi perceput prin perspectiva unei moșteniri culturale orientale bine conturate. Nu era pentru prima dată când romanii aveau de-a face cu astfel de culte și trebuiau să facă față și obiceiurilor orientale pe teritoriul lor, dat fiind faptul că o adoptaseră deja pe Mama Ideană împreună cu propriul ei chorus cinaedorum, fapt care i-a dezamăgit pe unii poeți precum Iuvenal. Dar să susțină pe deplin un suveran de tip oriental care încerca să le înlocuiască propriile valori cele ale sale, deja era un lucru greu de suportat. Cuvinte-cheie: Elagabalus, depravare, emasculare rituală, Bassiani, circumcizie